Proceedings of the Twentieth ACM International Symposium on Mobile Ad Hoc Networking and Computing 2019
DOI: 10.1145/3323679.3326503
|View full text |Cite
|
Sign up to set email alerts
|

DeepRadioID

Abstract: Network slicing of multi-access edge computing (MEC) resources is expected to be a pivotal technology to the success of 5G networks and beyond. The key challenge that sets MEC slicing apart from traditional resource allocation problems is that edge nodes depend on tightly-intertwined and strictly-constrained networking, computation and storage resources. Therefore, instantiating MEC slices without incurring in resource over-provisioning is hardly addressable with existing slicing algorithms. The main innovatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 95 publications
(34 citation statements)
references
References 62 publications
0
34
0
Order By: Relevance
“…An alternative approach that has recently gained traction in the research and industry communities is the concept of Radio Frequency Fingerprinting through Deep Learning (RFFDL). The RFFDL is as an emerging data-driven authentication approach that has shown promising results in authenticating IoT radios in a more energy-efficient and scalable fashion [2], [3], [4], [5], [6]. It relies on the hardwarelevel imperfections that are uniquely associated with the Radio Frequency (RF) analog circuitry of every single device, referred to as RF "fingerprint" or "signature".…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…An alternative approach that has recently gained traction in the research and industry communities is the concept of Radio Frequency Fingerprinting through Deep Learning (RFFDL). The RFFDL is as an emerging data-driven authentication approach that has shown promising results in authenticating IoT radios in a more energy-efficient and scalable fashion [2], [3], [4], [5], [6]. It relies on the hardwarelevel imperfections that are uniquely associated with the Radio Frequency (RF) analog circuitry of every single device, referred to as RF "fingerprint" or "signature".…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the promising progress in this domain, recent studies have revealed a number of challenges in developing robust and reliable RFFDL models for practical applications. Key among them are the non-stationary characteristic of the wireless channel and the dynamic nature of the environmental actions in a mobile scenario, which significantly limit fingerprinting accuracy by obscuring the hardware impairments associated with the transmitted waveform [2], [3], [7]. In particular, without intervention of sophisticated digital signal processing (DSP) algorithms, the existing RFFDL models suffer from significant performance degradation when training and testing of their deep learning classifier are done on separate segments of the data that are collected in different days/environments.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations